Of Divine Warning : Disaster in a Modern Age. - Gordon, Jane Anna (Radical imagination series., 2008)
"This book offers a theory of disaster in modern and contemporary society and its impact on the construction of social and political life. The theory is premised upon what the authors call "the sign continuum," where disaster spreads across society through efforts to evade social responsibility for its causes and consequences. Phenomena generated by such efforts include the social manifestation of monstrosity (disastrous people and other forms of living things) and an emerging antipolitics in an effort to assert rule and order. A crucial development is the attack on speech, a fundamental feature of political life, as manifested by the increased expectations of categories of people whose containment calls for shunning and silence. The book closes with an exploration of the significance of the mythic motif of eliminating monsters before dawn and its collapse in nihilistic times, where such conflicts now continue beyond dawn."--Jacket